An intelligent road traffic management system - Alam, Tahmid Tanzi; Chowdhury, Ahmad Naquib (BRAC University, 2016)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2016.